Baccharis napaea (Asteraceae, Astereae): a new species of subgen. Tarchonanthoides sect. Coridifoliae from the subtropical highlands of southern Brazil - Heiden, Gustavo; Pirani, José Rubens (Phytotaxa, 2012)
Baccharis napaea, a new species belonging to subgen. Tarchonanthoides sect. Coridifoliae is described and illustrated. The new species is compared to and distinguished from the sympatric species B. coridifolia, B. erigeroides, and B. scabrifolia, and from the allopatric B. bicolor. Baccharis napaea occurs in open subtropical highland grasslands and the edges and open glades of subtropical mixed forests on the south Brazilian plateau. Additionally, a distribution map and description of habitat and conservation status of the new species are presented.